PENGARUH SIKLUS KONVERSI KAS DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di ASEAN-5 Periode 2016-2020) - Errien Devitha; Irene Rini Demi Pangestuti (Diponegoro Journal of Management, 2022)
This research aims to examine the effect of cash conversion cycle and corporate governance on firm value. The independent variables of this research are proxied by cash conversion cycle, independent director, board size, audit committee size, frequency of board meeting, and then firm value measured by Tobin’s Q and Price to Book Value as dependent variable. In addition, firm growth, sales growth, firm size and leverage are used as a control variable. This research used secondary data and the population of this research is 450 manufacturing firms listed in the stock exchanges of the ASEAN-5 countries (Indonesia, Thailand, Philippines, Malaysia, and Singapore) for the period 2016-2020. By purposive sampling methods, 114 manufacturing firms were obtained as the sample of this research. This research used Generalized Least Square (GLS) to estimate the model parameters. The results of this research show that cash conversion cycle has a negative significant effect on firm value. Corporate governance variable which is board size has a negative significant effect on Tobin’s Q but insignificant on PBV. More, frequency of board meeting has a negative and significant effect on firm value. In addition, independent director and size of the audit committee variable has no impact on firm value